The impact of export activity and family nature on the innovativeness of SMEs - Szennay, Áron; Csákné Filep, Judit (Vezetéstudomány / Budapest Management Review, 2024)
Family businesses represent one of the oldest and still dominant forms of business organisations, yet research on their innovation activity remains a relatively emerging field of study, especially in Central and Eastern Europe. This paper investigates the relationships between the family nature of firms, the innovation activity and the export activity using statistical methods on a representative sample of Hungarian small- and medium-sized enterprises (SMEs) in 2017, 2020 and 2022. The results show that the innovation activity of Hungarian SMEs engaged in export activities is more significant than that of non-exporting counterparts. The family nature of firms and their innovation activity, however, can be considered independent, while the relationship between family nature and export activity is not consistent across the three years. A limitation is that the 2020 and 2022 surveys were performed during the first wave of the COVID-19 epidemic and the Russian-Ukrainian war, which may have influenced respondents.